Planeamento do treino de combate em ambiente urbano, utilizando realidade virtual e aumentada - Ramos, G. (2018)
Urban areas are increasingly the predominant combat scenario and pose great difficulties to military commanders due to their complexity, presence of civilians, unpredictability and difficulty of communication. The infrastructures of the Centre for Combat Training in Urban Environments of the School of Arms, of the Portuguese Army in Mafra, Portugal, are well suited for training of combat planning of small combat units, from platoon up to company level, with a building campus called "Aldeia Camões", a command and control room and a shooting range simulator, suitable for the use of national and international military and security forces. This is the appropriate place for development and testing of technologies that can increase training capabilities in the planning and execution of military operations in urban areas. This article presents the results obtained with a solution that uses Virtual and Augmented Reality technologies to support Planning of Combat Training in Urban Areas in the mentioned "Aldeia Camões" campus. This solution adopts the paradigm of the "virtual sandbox", which, in analogy with its physical version, allows both the classic visualization of the ground plan, its urban elements and forces in presence, as well as the switching for an exploration of the campus within a 3D virtual environment, in a first-person mode, supporting also annotations in both modes and several other tools to support the planning of training of military operations in urban environments.